The Effects of Nudging on Diversity and Inclusion: A Systematic Literature Review - Sara Mikaeili; Marco Tagliabue (Social Sciences, 2025)
Diversity and inclusion in organizational settings are still under-researched themes despite their societal relevance. In this preregistered systematic literature review, we examine how nudging as an agency-preserving intervention tool can create a more inclusive and diverse workplace. Nudging is rooted in behavioral economics and aims to influence decision-making processes without restricting freedom of choice. Inclusion refers to creating a work environment where everyone feels valued and encouraged to contribute. Diversity reaches beyond demographic factors, fostering more innovative and creative organizational practices, and better decisions. We searched for applications nudging towards diversity and inclusion initiatives at the workplace in four databases: PsycINFO, Scopus, EBSCOhost, and Web of Science. Peer-reviewed articles published in the last 15 years were included regardless of article type in organizational settings were included. Nine studies met our inclusion criteria. Based on their findings, we show a positive association between the use of nudging techniques to create more inclusive and diverse workplaces and advance a classification of nudge types in this domain. We discuss the importance of being aware of the potential drawbacks and negative consequences of using nudging interventions. Potential drawbacks that may arise include lack of autonomy and overload. Further research is needed to explore which nudging techniques are most effective in promoting diversity and inclusion.